Historias de fin de siglo: notas sobre la historiografía argentina de las últimas décadas - Palacio, Juan Manuel (Revista de historia., 2003)
This article provides a critical balance of the Argentinean historiography brought about since 1983, parting from the hypothesis that the recuperation of democracy in Argentina allowed for a renewal in the teaching of history. In addition to having created a general revision movement, it also gave rise to new issues. Nonetheless, important deficiencies exist, such as a keen, anti-Latin American bias that could be solved departing from the reinforcement of compared history in our subcontinent.